2022
DOI: 10.1021/acsaem.2c01035
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Planar Perovskite Solar Cells Using Lauric Acid as Interfacial Modifier

Abstract: Interfacial defect passivation of perovskite active layer has become an advantageous design that can alleviate interfacial nonradiative recombination, increase the stability and improve the performance of the device. Here, lauric acid as surface passivation agent is introduced on the top of a perovskite active layer. The carboxyl group (-COOH) on lauric acid can coordinate with the Pb2+ on the perovskite and passivate interface defects, which reduces carrier nonradiative combinations and enhances the photovolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…143 This has been attributed to the attractive properties of the –COOH functional group in coordination with the uncoordinated divalent cations of the perovskite films and their hydrogen bonding interactions, which are known to influence the crystallization quality of the perovskite film. 144 By using lauric acid as an interfacial modifier in the perovskite film, Yang's team was able to improve the performance and stability of PSCs significantly (ΔPCE = 3.28%). 144 The –COOH of lauric acid passivated in the surface defects leading to a reduction in non-radiative power losses whereas its alkyl chain improved the moisture resistance of the perovskite film, and hence the stability in the PSC.…”
Section: Natural Products As Additives In Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…143 This has been attributed to the attractive properties of the –COOH functional group in coordination with the uncoordinated divalent cations of the perovskite films and their hydrogen bonding interactions, which are known to influence the crystallization quality of the perovskite film. 144 By using lauric acid as an interfacial modifier in the perovskite film, Yang's team was able to improve the performance and stability of PSCs significantly (ΔPCE = 3.28%). 144 The –COOH of lauric acid passivated in the surface defects leading to a reduction in non-radiative power losses whereas its alkyl chain improved the moisture resistance of the perovskite film, and hence the stability in the PSC.…”
Section: Natural Products As Additives In Pscsmentioning
confidence: 99%
“…144 By using lauric acid as an interfacial modifier in the perovskite film, Yang's team was able to improve the performance and stability of PSCs significantly (ΔPCE = 3.28%). 144 The –COOH of lauric acid passivated in the surface defects leading to a reduction in non-radiative power losses whereas its alkyl chain improved the moisture resistance of the perovskite film, and hence the stability in the PSC. Fig.…”
Section: Natural Products As Additives In Pscsmentioning
confidence: 99%
“…47,48 The Ce-SnO x /perovskite film showed increased fraction A 1 , suggesting decreased nonradiative recombination, while the increased t 2 from 188 ns to 236 ns upon Ce doping could indicate a decrease in the recombination of free carriers or a suppression of defects forming in the perovskite film. 49 The suppressed nonradiative recombination may originate from the improved perovskite crystallization or decreased defect density induced by the passivation of the oxygen defects on the Ce-doped SnO x surface. 16 PSCs with pristine and Ce-doped SnO x ETLs were fabricated to study the effect of Ce doping on the device performance.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…Previous studies have shown that the V OC is affected by the native defects in polycrystalline perovskite films due to the overflowing of the organic components during the annealing process. [13][14][15] These defects induce nonradiative recombination, 13,[16][17][18][19] which leads to a shortened carrier lifetime and decreased V OC . 20,21 Therefore, reducing the trap states, especially the deep trap states, can decrease the charge recombination loss.…”
Section: Introductionmentioning
confidence: 99%